Encontro de palavras em procedimentos restaurativos uma visão possível sobre a linguagem e seu funcionamento - Dias, Ana Beatriz Ferreira (2014)
Wiht this research, we offer our counterwords to practices of restorative justice developed in instances of juvenile criminal justice. Restless with the tactics of prevention and solution of conflicts that are being proposed by the restorative justice, we look forward to comprehend language elements and their operation on a modality of meeting called Restorative Circle , usually considered the main part of restorative procedures. More specifically, this work deals with the possibility of finding, in restorative practices carried out on oficial justice system, what Ponzio understands by other word , a singular and free word, marked by the right of otherness. Thus, the objective of this work consists in put ourselves listening to other word on restorative practices inserted in a context dominated by retributive justice, hegemonic view in judiciary system. To do this work, we take as its central signical materiality audio and video records from two Restorative Circles that occurred in 2009, by the Programa Justiça para o Século XXI (Justice for the 21 Century Program), by the Central of Restorative Practices Court of Childhood and Youth, to support the activities of the Third Pole of Regional Court of Childhood and Youth in Porto Alegre, instance that is responsible by the execution of social and educational measures. The comprehensions of the texts are based on the theoreticalmethodological assumptions suggested by Bakhtin Circle, which are here developed according to the evidenciary research paradigm proposed by Ginzburg. Considering the interpretive path we have traced in this research, we divided the methodology in two great parts: steps of selection and steps of comprehension. The first one comprises a set of necessary actions on the beginning of this research, envolving, to this the selection of objective reality, from the choosing of the central materialities to the checking of the research feasibility. The second one refers to the set of methodological guidelines adopted to guide the comprehensions of the texts. This step was done based on the four necessary moments of analysis and interpretation of the texts proposed by Bakhtin and developed by Geraldi: 1) The perception of the material dimensions of sign in this work, the unity of perception was centered on the word as an ideological sign. 2) Its recognition. 3) The comprehension of its meaning in certain contexts. 4) The active-dialogic comprehension of the texts. Witht this work, we understand that the meeting of words in the Restorative Circles have ideological conditions and practices to contribute to both the deconstruction of the realities of the identity humanism, world view that sustains the dominant social relations, and the construction of a new humanism, the otherness one. Listening to the other word is a way tha could take to the humanization (the otherness humanism) of the social relations among victims, ofensors and their comunities of support, contribuiting, consequently, to the judiciary in order to reframe its actions.